Implementation of CIDOS (E-Learning) among Diploma in Accountancy students in Politeknik Sultan Abdul Halim Mu'adzam Shah, Jitra, Kedah - Razlina, Romli (2013)
This study aimed to determine the acceptance of accounting students in Politeknk Sultan Abdul Halim Mu'adzam Shah (POLIMAS) Jitra Kedah on the usage of e-learning in everyday life. This study investigates the effects the system of Curriculum Information Document Online System (CIDOS) in the learning environment as well as to determine the level of acceptance and usage of e-learning in the process of learning and education. This study is a pilot study examining the effects of e-learning in tertiary education system at the level diplomas of polytechnic in Malaysia. By using the questionnaire, a total of 100 students of the Diploma in Accountancy were selected. Students are asked to answer four sections of the questionnaire on demographic characteristics, ease of use, use of elearning and attitudes towards e-learning. Results show that CIDOS is well received among students but the systems needs encouragements from the instructors to achieve an effective utilization